Preparation of silver phosphate/graphitic carbon nitride via microwave irradiation for photodegradation of Rhodamine B / Nur Haslinda Hassan - Hassan, Nur Haslinda (2023)
Poor treatment of dyed wastewater could lead to serious water pollution and health problems. Photocatalysis is a high-impact method of reducing present environmental pollution on a big scale. Graphite phase carbon nitride g-C3N4 is a nonmetallic semiconductor photocatalyst that give significant advantages over other metal photocatalysts. However, there are limitations of g-C3N4 causing the photocatalytic activity slower. This issue can be overcome by coupling with silver phosphate. Research has been done on the synthesis of Silver Phosphate/graphitic Carbon Nitride (Ag3PO4/g-C3N4)using the microwave irradiation method, Ag3PO4/g-C3N4 material was applied as a photocatalyst to degrade Rhodamine B dye. Composite Ag3PO4/g-C3N4 synthesis was made by mixing Ag3PO4 and g-C3N4 in distilled water, which was then dried, then place in a microwave for 30 minutes at 450W. The results of the Ag3PO4/g-C3N4 synthesis were characterized using several instruments, including XRD FESEM, FTIR, and UV-Vis. The photocatalytic activity of the catalyst was observed in the degradation of Rhodamine B for 60 minutes using a 0.375 g/L catalyst. 10 CNAP shows the highest rate (95%) >5CNAP (82%)>Ag3PO4 (68%)>15CNAP (54%) > g-C3N4 (50%). Photocatalytic activity test using RhB was obtained that pH 6 as the optimum pH with a % degradation of 95%, obtained a concentration of 10 ppm as the optimum concentration with a % degradation of 95%, and obtained 0.5 g/L catalyst give the best performance degradation, 98%. For the scavenger, adding methanol to RhB, gives the highest percentage (93%). It shows that photogenerated H+ is crucial which decides this catalyst mechanism: Type II Heterojunction.